2022
DOI: 10.2147/oaem.s379543
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations of Human Atrial Natriuretic Peptide on Cardiac Function and Hemodynamics in Pediatric Septic Shock

Abstract: We aimed to determine the correlations of human Atrial Natriuretic Peptide (ANP) on cardiac function and hemodynamics in pediatric septic shock. Patients and Methods:We conducted an observational and prospective study on 30 children with septic shock. Measurement of the level of human atrial natriuretic peptide was determined in the serum of patients. Cardiac power (CP) is a cardiac function parameter measured with cardiac output (cardiovascular flow) and mean arterial (intravascular) pressure. Cardiac output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…From the hemodynamic parameters in this study, cardiac power was lowest at initial resuscitation and then increased progressively at 1, 6, and 24 h post-initial resuscitation. The cardiac power recorded in our study was similar to previous findings in children with septic shock, which showed an increased trend during the first three days after resuscitation [ 15 ]. The result reflected the typical clinical course of shock after initial resuscitation, where CO and MAP were optimized through fluids, vasoactive, and inotropic drugs [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From the hemodynamic parameters in this study, cardiac power was lowest at initial resuscitation and then increased progressively at 1, 6, and 24 h post-initial resuscitation. The cardiac power recorded in our study was similar to previous findings in children with septic shock, which showed an increased trend during the first three days after resuscitation [ 15 ]. The result reflected the typical clinical course of shock after initial resuscitation, where CO and MAP were optimized through fluids, vasoactive, and inotropic drugs [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…Based on previous studies in Indonesia, the proportion of septic shock was 51%, while the mean cardiac power and lactate clearance in children with septic shock on day 1 were 0.38 ± 0.35 and 44.17 ± 24.28%, respectively [ 4 , 15 , 16 ]. Therefore, with α of 5% and a margin of error of 15%, the sample size would be 44 children.…”
Section: Methodsmentioning
confidence: 99%
“…54 Higher pro-ANP levels, which could result from lower levels of CORIN, are associated with poor survival prognosis in children and adults with severe sepsis and septic shock. 55,56 The lower levels of CORIN we observed could therefore result in higher levels of pro-ANP and lower levels of ANP, which could contribute to the hypertension, inflammation and cardiac manifestations associated with severity and shock in MIS-C. Future studies to measure the ratio of pro-ANP to ANP levels in MIS-C could provide insight into the disease mechanisms and help in validating our findings. While the best performing diagnostic biomarkers (PCSK9, CD163 and CXCL9) were significantly elevated in MIS-C patients, they were not found to be associated with severity of MIS-C.…”
Section: Discussionmentioning
confidence: 68%
“…Most of the patients in this study showed normal cardiac output (CO). Together with blood pressure, CO determines the prognosis of some critical illnesses and becomes a significant component in the diagnosis of cardiogenic shock (14). As mentioned in the previous parts, CO is the product of SV and HR.…”
Section: Discussionmentioning
confidence: 95%